Female Protagonists in Current and Modern English Novels Written by Kamala Markandaya: Exploring Spiritual Themes and Female Protagonists in Kamala Markandaya's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The spiritual undercurrents of Indian culture are revealed in the books of Kamala Markandaya,which are defined by their profound cultural and emotional relevance. This research delves into thespiritual topics that Markandaya addresses, including compassion, self-discovery, and the quest formeaning in an ever-shifting environment. Her heroes' quests for personal growth and enlightenmenttypically take the guise of epic adventures. The research explores how the protagonists in Shobha De'scontemporary tales deal with spiritual issues as they navigate the fast-paced metropolitan world. Theresults of this research add to our knowledge of the many faces that spirituality takes throughoutliterature.